KEBERTAHANAN KOSAKATA BAHASA KULISUSU DALAM LINGKUNGAN PERTANIAN TRADISIONAL PADA REMAJA DESA LABELETE KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Tili Fendriani; Wa Ode Halfian (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research was chosen with the purpose to determine the level of the survival of vocabulary Kulisusu Language in the traditional agricultural environment. Subjects in this study were adolescents with aged 18-21 year olds, who were in the Labelete Village Sub-district North Kulisusu North Buton regency. In this study took 50 respondents and submitted a questionnaire containing 60 Vocabulary in the traditional agricultural environment (one questionnaire). The method that used in this study was qualitative and quantitative methods. Based on the results and discussion in this study, among the 60 vocabulary words (one questionnaire) submitted to 50 respondents it can be conclude that the level of survival of the vocabulary of each respondent is two respondents who still know the entire vocabulary of the Kulisusu language in the traditional agricultural environment of 100% traditional agricultural equipment namely respondents 1 and 2. The level survival of the vocabulary all respondents, there are ten vocabulary that are still known by all respondents (50 respondents) because the tenth of vocabulary are still often use in everyday life. And the level of the survival vocabulary Kulisusu language in the traditional agricultural environment containe in the research questionnaire as many as 60 vocabulary (1 questionnaire) submitted to 50 respondents survive with a survival rate of 71.23% overall. Keywords: Defense, Vocabulary, Traditional Agricultural environment